Choline phosphate functionalized cellulose membrane: A potential hemostatic dressing based on a unique bioadhesion mechanism. (August 2016) - Yang, Xiaoqiang; Li, Na; Constantinesco, Iren; Yu, Kai; Kizhakkedathu, Jayachandran N.; Brooks, Donald E.
Graphical abstract: Abstract: Wound dressings are a key component in provision of optimal conditions for bleeding control and wound healing. For absorbent dressings, electrostatic interactions are frequently utilized as one of the mechanisms driving dressing adhesion. Herein, a choline phosphate functionalized biocompatible cellulose membrane that can efficiently arrest human red blood cells was developed to have potential application in wound dressing. The bioadhesion is based on the unique multivalent electrostatic interaction between the head groups of phosphatidyl choline based lipids on the cell membrane and its inverse orientation but virtually identical structure, choline phosphate, coupled to the cellulose membrane. For functionalization, the cellulose membrane was decorated with polymer brushes bearing multiple choline phosphate groups via surface-initiator atom transfer radical polymerization followed by click chemistry. The modified cellulose membranes were characterized by ATR-FTIR and the molecular weight and the grafting density of polymer brushes grafted from the cellulose membrane surface were thoroughly evaluated by calibrated force-distance measurements with atomic force microscopy (AFM). This new method provides an approach to estimating polymer brush parameters on rough surfaces of unknown surface area based on the dependence of brush thickness on brush density and polymer molecular weight for a calibration set of brushes. The dependence of binding of human red blood cells (RBCs) to the cellulose membrane surface on the number density of choline phosphate groups (e.g. molecular weight) and the grafting density were investigated using this AFM-based approach. Bound RBCs showed "pseudopodia"-like membrane projections under scanning electron microscopy where cells contacted the microfibers of the cellulose, distorting the RBC shape, reflecting the multivalent interactions between the RBCs and the choline phosphate-doped cellulose membrane. We believe this efficient strategy provides a promising approach to blood conservation and trauma management. Statement of Significance: Uncontrolled bleeding can dramatically affect morbidity and mortality. Absorptive wound dressings provide either adherent or non-adherent layers to control bleeding. Our new adherent material is based on a universal adhesion reaction between cell membrane phosphatidyl choline (PC) headgroups and cellulose membranes (CM) decorated with polymer brushes carrying a CP group per monomer. The CP-PC multivalent interactions provide adherence to cut tissue margins and blood cells, blocking bleeding. We here demonstrate the strong specific binding of red cells to CM-CP but not CM-PC membranes and determine the requisite brush molecular weight and surface concentration via a new approach using atomic force microscopy, applicable to rough surfaces. We believe this strategy provides a promising approach to blood conservation and trauma management.